Abundance and relative growth of Donax denticulatus (Bivalvia: Donacidae) at Levisa Beach, Southeastern Cuba - Ocaña, Frank A. (2015)
This paper is aimed at describing spatio-temporal variation in abundance, size structure and length-weight relationship of a Donax denticulatus population at Levisa Beach on the Southeastern coast of Cuba. From April to September 2008, monthly samples were collected from four stations located along the beach; three strata were established across the intertidal zone of each station. Three replicate sediment samples were collected from each stratum with a 0.025 m2 PVC corer and sieved with a 1 mm mesh. Mean density ranged from 612.2 to 1366.7 ind. m-2, and no differences were found among the sampled months but rather among strata. There is a relationship between the abundance of recruits, young and adults, and strata. The middle intertidal zone showed the highest proportion of individuals, mainly young and adults. Monthly length frequencies showed that recruits appeared in April and May. Length-weight relationship showed a significant correlation between these variables; however, the allometric coefficient value is different considering different life stages. This population shows potential to be exploited, but some management measures proposed in this paper must be taken into account to ensure sustainability.